Women's drug use in everyday life - Eleonorasdotter, Emma (Palgrave Macmillan, 2024)
This open access book explores the increasing role of psychoactive substances in contemporary everyday life, focussing on women's use. Drawing on an ethnographic study in Sweden, it uses cultural studies and queer phenomenology to analyse the women's narratives of drug use relating to themes that encompass social, legal, cultural, embodied and gendered perspectives on drugs in the contemporary Western world. It examines topics such as stigma, happiness, children, the body, gifts, the drug market, medication, sickness and health and also the orientation of themselves towards others, to social and cultural norms, to drug laws and to the substances. It discusses how drug related spaces and directions be analysed in terms of gender and class, and how, in turn, the directions of contemporary society and culture can be affected by drug use. It speaks to academics in Sociology, Criminology, Ethnology, Gender studies, Law and History